Introduction to proteins : structure, function, and motion - Kessel, Amit; Ben-Tal, Nir (Boca Raton, Florida : CRC Press/Taylor & Francis Group, 2011)
"The book aims to provide the reader with a detailed description of protein structure and dynamics, combined with an in-depth discussion of the relationship between both these aspects and protein function. Adopting the structural-biophysical approach, we discuss these in relation to molecular interactions and thermodynamic changes that transpire in this highly complex system. There are several types of textbooks describing protein structure and function. Biochemistry textbooks emphasize the functional aspect of proteins and provide a rather general description of structure and structure-function relationship (SFR). Structural Biology textbooks provide an extensive description of protein structure and also refer to SFR with varying degrees of detail. However, energy-related aspects are often avoided. Molecular biophysics textbooks focus on molecular interactions and thermodynamic aspects of protein structure, but tend to lack detailed description of structural and dynamic aspects, as well as SFR. Our book refers to all of the aforementioned aspects and attempts to provide a unified view. Our energy-oriented approach is manifested throughout the book, whether we discuss structure, dynamics or specific functions of proteins. An extensive discussion of the energetics of protein structure is also given in a chapter dedicated to this topic"--Provided by publisher
1. Introduction -- 2. Protein structure -- 3. Methods of structure determination and prediction -- 4. Energetics and protein stability -- 5. Protein structural dynamics -- 6. Non-globular proteins -- 7. Membrane proteins -- 8. Protein-ligand interactions
Includes bibliographical references and index
Keywords: Physical biochemistry; Proteins; Proteins -- Structure-activity relationships; Proteins -- physiology; Amino Acid Sequence; Protein Conformation